Regions in the United States and the European Union - GDP per Capita, Convergence Processes and Spatial Dependencies - Folfas, Paweł (Studia Oeconomica Posnaniensia, 2017)
Forthcoming Transatlantic Trade and Investment Partnership may become a crucial element in the post-crisis world of economics and politics. Consequently, it is worth scrutinizing the economic performances of the United States and the European Union. This paper is aimed at answering the question of whether absolute GDP per capita beta-convergence exists in the case of regions of the United States (US counties) and in the case of regions of the EU-28 (NUTS 3) during the period of 2000-2011 and where (in the United States or in the EU-28) speed of convergence used to be faster. The research is based on econometric models, namely on the spatial lagged model (SLM) and spatial error (SEM) which contrary to ordinary the least squares (OLS) model include spatial dependencies. The SLM and SEM models detect the absolute GDP per capita beta-convergence among regions of US and among regions of the EU-28.During the period of 2000-2011 the average annual speed of convergence among regions in US was faster than between the regions of the EU-28. Moreover, according to the statistical analysis the EU-28 regions are characterized by stronger spatial dependencies than regions of the United States. But disparities (according to the results of general sigma-convergence analysis) among the EU-28 regions are bigger than among the US regions.